Effects of the cryopreservation process on dog sperm integrity - Sicherle, Carmen Cecilia [UNESP]; Souza, Fabiana Ferreira de [UNESP]; Freitas-Dell'Aqua, Camila de Paula [UNESP]; Mothe, Gabriele Barros [UNESP]; Padovani, Carlos Roberto [UNESP]; Papa, Frederico Ozanam [UNESP]; Lopes, Maria Denise [UNESP] (Brazilian Coll Animal Reproduction, 2020)
Sperm cryopreservation has become an indispensable tool in reproductive biology. However, frozen/thawed semen has a short lifespan due to loss of sperm cell integrity. To better understand which sperm cell structures are compromised by the cryopreservation process and apoptosis markers, the sperm of five healthy mature dogs was analyzed in this study. Analysis was performed after collection, cooling, and thawing via computer assisted sperm analyzer (CASA) and evaluation of membrane fluidity and permeability, phosphatidylserine translocation (Annexin V), membrane integrity, mitochondrial membrane potential, membrane lipid peroxidation (LPO) and activity of the apoptotic markers caspases 3 and 7 by flow cytometry. Cryopreservation decreased total and progressive motility and the percentage of rapid sperm (P < 0.01). Damage to sperm cells was confirmed by Annexin V (P < 0.01), indicating that capacitation-like changes were induced by the cryopreservation procedures. An increase in sperm membrane fluidity was also noted in frozen/thawed samples (P < 0.01). Plasma and acrosomal cell membranes were affected (P < 0.01), with decreases in the subpopulation displaying high membrane potential (P < 0.01). Membrane LPO was increased in thawed sperm compared to cooled sperm (P < 0.05) but was not different from that in fresh sperm. No differences were observed in caspase 3 and 7 activity after cooling, freezing, or thawing. In conclusion, total and progressive motility, plasma membrane integrity and mitochondrial membrane potential suffered from the deleterious effects caused by cryopreservation, unlike the activity of caspases that remained stable during the freezing process.
Keywords: dog; spermatozoa; cryopreservation; sperm quality; cell integrity